Nanosecond Dynamics Regulate the MIF‐Induced Activity of CD74. Issue 24 (9th May 2018) - Pantouris, Georgios; Ho, Junming; Shah, Dilip; Syed, Mansoor Ali; Leng, Lin; Bhandari, Vineet; Bucala, Richard; Batista, Victor S.; Loria, J. Patrick; Lolis, Elias J.
Abstract: Macrophage migration inhibitory factor (MIF) activates CD74, which leads to severe disorders including inflammation, autoimmune diseases and cancer under pathological conditions. Molecular dynamics (MD) simulations up to one microsecond revealed dynamical correlation between a residue located at the opening of one end of the MIF solvent channel, previously thought to be a consequence of homotrimerization, and residues in a distal region responsible for CD74 activation. Experiments verified the allosteric regulatory site and identified a pathway to this site via the MIF β‐strands. The reported findings provide fundamental insights on a dynamic mechanism that controls the MIF‐induced activation of CD74. Abstract : Molecular dynamics (MD) simulations up to one microsecond revealed dynamical correlation between a residue located at the opening of one end of the macrophage migration inhibitory factor (MIF) solvent channel, previously thought to be a consequence of homotrimerization, and residues in a distal region responsible for CD74 activation. Experiments verified the MIF allosteric regulatory site and identified a pathway to the CD74 activation site via β‐strands.